Relationship Between Performance of Carob Moth, Ectomyelois ceratoniae Zeller (Lepidoptera: Pyralidae) and Phytochemical Metabolites in Various Pomegranate Cultivars - Abedi, Zahra; Golizadeh, Ali; Soufbaf, Mahmoud; Hassanpour, Mahdi; Jafari-Nodoushan, Ali; Akhavan, Hamid-Reza (Frontiers in Physiology, 2019)
The carob moth, Ectomyelois ceratoniae Zeller (Lepidoptera: Pyralidae), is the main pest of pomegranate, Punica granatum L., in Iran and many parts of the world. In this study, the effects of 11 commercial cultivars of pomegranate (Aban-Mahi, Esfahani-Daneghermez, Gabri, Gorche-Tafti, Malase-Danesyah, Malase-Yazdi, Shahvare-Daneghermez, Shahvare-Danesefid, Tabolarze-Mehrmahi, Tafti, and Toghe-Gardan) were evaluated on life history variables, nutritional performance, and energy reserves of E. ceratoniae under the following laboratory conditions: 30±1°C, 60±5% RH, and a photoperiod of 14:10 (L:D) hours. In addition, biochemical characteristics of the tested cultivars were assessed in order to understand any possible correlation between important demographic parameters and nutritional properties with biochemical features of pomegranate juice. Our research showed that various pomegranate cultivars have significant effects on life history, demographical parameters, nutritional indices, and energy reserves of E. ceratoniae. The shortest development time was observed on Shahvare-Danesefid cultivar and the longest was on Esfahani-Daneghermez and Malase-Danesyah cultivars. The highest intrinsic rate of increase (rm) was observed on Shahvare-Danesefid and the lowest was on Esfahani-Daneghermez. Six major anthocyanin compounds were detected in juice of various pomegranate cultivars. Significant positive or negative correlations were observed between life history variables and nutritional characteristics with biochemical traits of pomegranate cultivars. The results indicated that Shahvare-Danesefid was a relatively susceptible pomegranate cultivar and Esfahani-Daneghermez was the least appropriate (most resistant) cultivar for feeding of E. ceratoniae, which could be useful in the development of integrated pest management strategies for this pest.